Anatomic Patterns of Recurrence Following Biochemical Relapse in the Dose-Escalation Era for Prostate Patients Undergoing External Beam Radiotherapy - Zumsteg, Zachary S. (J Urol, 2015)
PURPOSE: To provide a comprehensive analysis of anatomic patterns of recurrence following external beam radiotherapy (EBRT) for localized prostate cancer (PC) patients. MATERIALS AND METHODS: This retrospective analysis included 2694 patients with localized PC receiving definitive dose-escalated EBRT from 1991 to 2008. First-recurrence sites (FRS) were defined as initial sites of clinically detected recurrence (CDR) and any subsequent CDR within 3 months. Anatomic recurrence patterns were classified as local (prostate/seminal vesicles only), lymphotropic (lymph nodes [LN] only), and osteotropic (bones only) for patients with disease confined solely to these respective sites for at least 2 years from initial CDR. RESULTS: Prostate was the most common FRS for all risk groups (8-year cumulative incidence, 3.5%, 9.8%, and 14.6% for low-, intermediate-, and high-risk patients, respectively). Eight-year risk of isolated pelvic LN relapse as FRS was 0%, 1.0%, and 3.3%, respectively. For the 474 patients experiencing CDR, the most common FRSs were local (55.3%), bones (33.5%), pelvic LN (21.3%), and abdominal LN (9.1%). Patients displayed unique relapse distributions, including local (41.6%), lymphotropic (9.7%), osteotropic (20.3%), and multiorgan/visceral (28.5%) patterns. Anatomic recurrence pattern was the strongest predictor for PCSM in a multivariate analysis of CDR patients. CONCLUSIONS: The most common FRS after dose-escalated EBRT for PC is within the prostate and SV for all risk groups. By contrast, patients treated without elective pelvic LN irradiation have a relatively low risk of isolated pelvic LN relapse. Recurrence patterns displayed a tropism for specific anatomic distributions, with divergent prognoses, suggesting underlying biological differences amongst tumors.